2016
DOI: 10.1007/s10903-016-0499-7
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Trauma in Refugee Families: A Systematic Review

Abstract: Although a robust literature describes the intergenerational effects of traumatic experiences in various populations, evidence specific to refugee families is scattered and contains wide variations in approaches for examining intergenerational trauma. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria, the purpose of this systematic review was to describe the methodologies and findings of peer-reviewed literature regarding intergenerational trauma in refugee families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(122 citation statements)
references
References 38 publications
4
116
0
2
Order By: Relevance
“…Our results are congruent with the findings of Daud et al [19] that offspring of Arabic speaking refugee parents with PTSD in Sweden scored lower on an IQ-test compared with offspring of Arabic-speaking parents without PTSD. As demonstrated in previous research, post-traumatic stress extends beyond the individual to family members and can be experienced as a common trauma in the family, where parents' reactions to traumatic experiences and the child's own perception of these experiences may affect the child's wellbeing and mental health [15]. Parental experience of traumatic stress may lead to a lack of consistency and stability in the family and has been associated with disconnected and insensitive parenting behaviour and harsh parenting styles [11,12,25,26].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Our results are congruent with the findings of Daud et al [19] that offspring of Arabic speaking refugee parents with PTSD in Sweden scored lower on an IQ-test compared with offspring of Arabic-speaking parents without PTSD. As demonstrated in previous research, post-traumatic stress extends beyond the individual to family members and can be experienced as a common trauma in the family, where parents' reactions to traumatic experiences and the child's own perception of these experiences may affect the child's wellbeing and mental health [15]. Parental experience of traumatic stress may lead to a lack of consistency and stability in the family and has been associated with disconnected and insensitive parenting behaviour and harsh parenting styles [11,12,25,26].…”
Section: Discussionmentioning
confidence: 84%
“…This review also indicated an association between parental PTSD symptoms and parent-child functioning difficulties, such as communication problems and less positive parental engagement [14]. Another systematic review focusing on intergenerational effects of trauma in refugee families demonstrate that the effect on children was diverse but mostly negative [15]. The majority of studies showed that children in refugee families, where a parent suffers from psychological consequences after having experienced trauma, are at increased risk of adverse psychological outcomes and vulnerability to psychosocial stress, including posttraumatic stress, mood, and anxiety disorder symptoms, and at greater risk of abuse and neglect [15].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…There is a considerable number of publications on psychological aspects and care management regarding displaced children (Joshi & Fayyad, 2015;Gaudichon et al, 2017), issues related to refugee child mental health and disorder from the angle of social justice (Chung et al 2008;Eytan et al, 2002;Nielsen et al, 2008), analysis of intergenerational trauma in refugee families (Sangalang & Vang, 2016).…”
Section: Academic Frameworkmentioning
confidence: 99%